Prognostic Role of Tumor Mutational Burden in Cancer Patients Treated With Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis - Huang, Taobi; Chen, Xia; Zhang, Huiyun; Liang, Yuan; Li, Longquan; Wei, Hui; Sun, Weiming; Wang, Yuping (Frontiers in Oncology, 2021)
Purpose: Immunotherapy is regarded as the most promising treatment for cancer. However, immune checkpoint inhibitor (ICI) is not effective for all patients. Here, we conducted a systematic review and meta-analysis to explore whether TMB can be used as a potential prognostic biomarker for cancer patients treated with ICIs. Methods: We systematically retrieved the qualified literatures published in PubMed, Embase, Web of Science, and Cochrane databases up to December 28, 2020. All cohort studies and clinical trials that reported hazard ratio (HR) for overall survival (OS) and progression-free survival (PFS), as well as corresponding 95% confidence interval (CI) of patients with high TMB and low TMB were included. All statistical analyses were performed with R software. Results: The pooled results from 32 studies with 6131 participants showed significantly increased OS (HR 0.61, 95% CI 0.53 to 0.71; P < 0.01) and PFS (HR 0.51, 95% CI 0.44 to 0.60; P < 0.01) for high TMB group receiving ICIs compared with low TMB group. Particularly, the results from studies with larger sample size (≥30), western patients, higher cutpoint value of TMB (≥20 mut/Mb), anti-PD-1 therapy, and when the sample source was tissue and tumor type was melanoma, small cell lung cancer or gastric cancer, were more significant. Conclusion: TMB was promising to be an independent prognostic biomarker for cancer patients receiving ICIs. It could provide a new potential therapeutic idea for high TMB patients who failed in traditional therapy.